The 6th nationwide anthropological survey of children and adolescents in the Czech Republic in 2001 - Kobzová, Jarmila; Vignerová, Jana; Bláha, Pavel; Krejčovský, Lubomír; Riedlová, Jitka (Central European Journal of Public Health, 2004)
The 6th nationwide anthropological survey (NAS) of children and adolescents was carried out in the Czech Republic in 2001 to continue the series of surveys repeated at 10-year intervals since 1951 (with the participation of the Slovak Republic up to 1991). The major objective was to find out the following body measurements of children and adolescents: body height and weight, and head, arm, waist and hip circumferences. Questionnaires were used to find out the body measurements of parents (body height and weight) and some socio-economic characteristics of the child's family (number of siblings, education of parents, breast feeding duration, birth weight and length, child's physical activities, TV watching time, computer gaming time, etc.). A school children questionnaire focused on eating habits was also part of the survey in 2001. A total of 59,000 children aged 0.00 to 18.99 years, i.e. about 3% of the population of the same age range, were enrolled in the survey in 2001. The results obtained presented in diagrammatic and tabular forms are reference standards for monitoring growth of the Czech children and adolescents from birth to the age of 19 years. The survey revealed a substantial slowdown in the long-term trend in body height increase for both boys and girls. The most marked increase in the mean body height is currently recorded in boys at the prepubescent age while the pubescent girls show a practically zero increase for this parameter. A more marked increase in body height at the adult age is not expected any more, but the increase in body height and weight at the prepubescent age is likely to continue for some time. The 6th NAS showed a marked slow down to a stop in the trend in the mean body weight increase. No increase in the mean body weight has been recorded in pubescent girls since the 1970's and in pubescent and postpubescent boys since 1991. Nevertheless, the younger age groups, namely those of preschool and primary school children, continue to show increase in the mean body weight. The secular trend in body weight has been less pronounced compared to that in body height. The rates of overweight and obese children (as assessed by body mass index, BMI) have risen in most age groups of school children compared to those reported in 1991. In contrast, a slight decrease in the rate of overweight children can be seen in boys starting from the age of 16 years and in girls starting from the age of 13 years. The obesity prevalence rate is significantly higher in boys than girls. Statistical analysis confirmed a correlation between the BMI values in children and education of parents (the higher the education, the lower the rate of overweight children) and between the BMI values and the population size of the community where the child lives (the higher the population, the lower the prevalence rates of overweight and obesity). Single children suffer more frequently from overweight and obesity than those with siblings.
Keywords: tělesná hmotnost; Obesity; Humans; Research Support as Topic; Body Height; Czech Republic; finanční podpora výzkumu jako téma; populační růst; mužské pohlaví; Česká republika; antropometrie; Adolescent; Anthropometry; ženské pohlaví; lidé; mladiství; Body Weight; Population Growth; dítě; tělesná výška; Child; Male; obezita; Female